PP.16.20: CORRELATIONS BETWEEN SERUM THIOCYANATES AND HEART RISK FACTORS IN THE HISTORICAL BRISIGHELLA HEART STUDY COHORT. (June 2015) - Cicero, A.G.; Parini, A.; Rosticci, M.; Cagnati, M.; Grandi, E.; D'Addato, S.; Borghi, C.; Group, Bhs
Abstract : Objective: Thiocyanates are a group of small and highly acid pseudohalogens, ubiquitary in mammalian fluids. While the assumption of thiocyanates by food (especially with highly cyanogen plants such as cruciferous vegetables) seems to be associated to positive health outcomes, the one derived by endogenous production have a less clear biological signification. Usually the serum thiocyanates levels are higher than in smokers than in non-smokers, as a possible defensive system against oxidative stress. Design and method: We selected from the general database of the Brisighella Heart Study a sample of non-pharmacologically treated adult subjects, in primary prevention for cardiovascular disease, without known allergic nor rheumatological disease, not assuming antioxidant dietary supplements, visited during the same population survey. A full set of clinical and ematochemistry parameters has been evaluated together with the serum level of thyocianates. Results: In our study thiocyanates levels were significantly higher in smokers, proportionally to the number of cigarettes smoked per day. No significant differences were shown between former smokers and non-smokers. No significant differences to thiocyanates serum levels were shown due to food habits or due to renal function. Thiocyanates levels were lower in those patients with hypertension. People with thiocyanates lower than the median (74, 5 microMOL/L) were more used to die for cardiovascular events; this evidence was stronger in non-smokers (p < 0, 001), while was not significant in smokers (p = 0, 84). The ROC curve showed that the dosage of thiocyanates was a predictive test for non-event in non-smokers (cut off = 74, 5 microMOL/L). Thiocyanates identified a lower probability of being affected by hypertension in men (OR 0, 61 p = 0, 016). Conclusions: Our data seems to confirm a protective role of serum thicyanates toward cardiovascular risk in non-smokers, but not in smokers.